Cardiac sarcoidosis – silent destroyer. - Martusewicz-Boros, Magdalena M; Piotrowska-Kownacka, Dorota; Wiatr, Elżbieta; Roszkowski-Śliż, Kazimierz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
We report a case of histologically proven pulmonary sarcoidosis and cardiac involvement in a 53-year old woman with progression leading to the heart failure documented in cardiovascular magnetic resonsnce studies.